ANALISIS HUKUM EKONOMI SYARI’AH TERHADAP PEMBOIKOTAN PRODUK ISRAEL - Audara Laili; Muhammad Iqbal Fasa; A. Khumaidi Ja’far (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
Plans to boycott American products must take into account the national economy. American products have contributed to increasing national economic growth, because Indonesia's human and natural resource management has so far depended on American products. Boycott actions will reduce economic growth, because it will decrease demand and increase unemployment. In addition, his actions, on the one hand, will not be effective because the economic relations between Indonesia and the United States have been ratified by regional and international trade organizations. On the other hand, Indonesia's dependence on American products is relatively high, as can be seen from the volume of non-oil and gas exports and imports of the two countries. The government's economic policy is influenced by cooperation with other countries, and therefore, the boycott action will not affect the decline in consumption of American products.